An Evaluation Model of Problem-Based Learner Assessment in Curriculum 2013 - Wijayanti, Yunita Rizky (Indonesian Journal of English Language Studies (IJELS), 2015)
Curriculum 2013 has just been implemented at schools in Indonesia, and its implementationhas brought pros and cons among academicians. One of the major constructive criticismsrelated to the implementation of curriculum 2013 deals with the application of the creation.Bloom claims that creating places the top level among the thinking skills (Pohl, 2000).Furthermore, Dyers (2011) states that the main goal of each learning process is to improvethe learners‟ creativity. This paper focuses on the evaluation of learner assessment; hence, itaims to propose an alternative model of learner assessment based on curriculum 2013 byfocusing on the concept of scientific approach especially on creation and also the concept ofpositivism. Moreover, the result of Forum Group Discussion (FGD) shows positive feedback.The findings obtained from FGD generally show more positive feedback than the negativeone. In brief, it can be concluded that the model has been better because it provides creation,clear description, and it may encourage building positive characters of the learners.Keywords: evaluation model, problem based, learner assessment, creation, scientific approach, positivism